Genomic medicine in the prevention and treatment of atherosclerotic cardiovascular disease. (June 2012) - Tuteja, Sony; Rader, Daniel J
Cardiovascular disease (CVD) is the leading cause of death in the world. Over the past decade considerable progress has been made in understanding the genomic basis of polygenic disorders including CVD. The future application of genomic medicine to the prevention and treatment of CVDs will ultimately lessen the burden of CVD. Given the complex nature of CVD, information derived from newer evolving fields, such as transcriptomics, proteomics and metabolomics, will allow us to fully interrogate features of the human genome to better understand disease pathogenesis and to identify new drug targets. In this article, we will review how genomics will allow enhanced risk prediction of cardiovascular events, provide personalized treatment options and hasten the drug development process, with a particular focus on atherosclerotic CVD.